The Effect Of Kegel Exercise In The Recovery Process Of Postpartum Mothers With Normal Delivery At Rismala Clinic, West Kisaran District - Nani Jahriani; Ririn Anggriani Sitorus; Emah Rohemah; Primastuti Widyaningrum (Sean Institute, 2024)
Latar Background: Pada during pregnancy sebaiknya the breast should have been perhatian a particular concern kebersihan breast hygiene and bentuk puting nipple shape is flat or entered into. Puting susu Such nipples are actually not an obstacle for mothers to breastfeed dengan well by knowing from the beginning, mothers have time to work so puting that the nipples are easier when breastfeeding. Besides that, it is also very important to pay attention kebersihan persoalanto hygiene issues (Rustarmadji, 2018)..Purpose of the study: Tujuan the general purpose of this study ini was to determine the level of knowledge of mothers about BreastCare Payudara During Pregnancy. Metode This research method ini is descriptive research using crossectional methodcrossectional. The population of 40 pregnant women in the clinic Armiyanti range, sampling was done with Total samplinga Total sampling with a sample of 40 respondents. Data retrieval using primary data with observation instruments. Analysis using univariate and bivariate. Results: the results of 40 respondents can be concluded respondents well informed as many as 22 people (55.0%), knowledgeable enough as many as 11 people (27.5%) and knowledgeable less as many as 7 people (17.5%). Conclusion: seen the level of knowledge of paydara care in pregnant women based on education, age, work etc.